1993
DOI: 10.1002/jso.2930520110
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of esophageal carcinoma in patients eighty years of age and older

Abstract: Before 1979, no patient 80 years of age or older had been operated on at our institution for esophageal cancer, while in the middle period (1980-1984), three patients were operated on, and postoperative pulmonary complications and operative death occurred in 66.7 and 33.3%, respectively. However, in the recent period (1985-1990), there was no postoperative morbidity or mortality in the five cases over age 80. On the other hand, there were 12 patients over age 80 who did not undergo operation, of whom all died … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…A literature search on head and neck surgery revealed studies of outcome vs age in acoustic neuroma, thyroid, and laryngeal surgery that warn against minimal palliative approaches and cite comparable results to morbidity and mortality in younger patients. [15][16][17][18] Our study demonstrated results in accordance with this recent literature. Age 70 years or older was not related to postoperative complications or hospital LOS in any of the multivariate analyses.…”
Section: Commentsupporting
confidence: 96%
“…A literature search on head and neck surgery revealed studies of outcome vs age in acoustic neuroma, thyroid, and laryngeal surgery that warn against minimal palliative approaches and cite comparable results to morbidity and mortality in younger patients. [15][16][17][18] Our study demonstrated results in accordance with this recent literature. Age 70 years or older was not related to postoperative complications or hospital LOS in any of the multivariate analyses.…”
Section: Commentsupporting
confidence: 96%
“…In octogenarians, it is believed that preoperative comorbidity is more common and more intensive perioperative management may be required 19,20 . In Japanese octogenarians with cancer of other organs, such as esophagus, 19,21 stomach, 20 and lungs, 22 surgical interventions have become much safer without an increase in morbidity and mortality. Eighty‐year‐old males and females in Japan have average life expectancies of 8.7 years and 11.7 years, respectively, 23 and elderly population 80 years or older in Japan will reach eight million in 2010.…”
Section: Discussionmentioning
confidence: 99%
“…144 More contemporary, albeit small series, suggest that age alone should not be used as a selection criteria not to undergo esophageal resection. 145 Unfortunately, many older patients are poor operative risks, and often the disease is unresectable at the time of diagnosis. Computed tomographic scanning and endoscopic ultrasonography should be used to determine respectability and to stage the tumor.…”
Section: Esophageal Cancermentioning
confidence: 99%